2017
DOI: 10.3832/ifor2209-010
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Chamber: a useful tool to monitor the CO2 exchange dynamics of shrubland

Abstract: A transient state canopy-chamber was developed to monitor CO2 exchange of shrubland ecosystems. The chamber covered 0.64 m 2 and it was modular with a variable height. Several tests were carried out to check the potential errors in the flux estimates due to leakages and the environment modifications during the measurements inside the chamber. The laboratory leakages test showed an error below 1% of the flux; the temperature increases inside the chamber were below 1.3 °C at different light intensity and small p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The selection of observation time for chamber measurements was empirical in the literature. For instance, the observation length of CO 2 flux estimation ranged between 1.5 min to 10 min (Wohlfahrt et al, 2005; Kutzbach et al, 2007; Savage et al, 2008; Koskinen et al, 2014; Görres et al, 2016; Guidolotti et al, 2017; Kostyanovsky et al, 2018), and that of other green house gases such as CH 4 and N 2 O ranged between 10 min to 25 min (Hendriks et al, 2007; Kroon et al, 2008; Savage et al, 2014). Most of the published studies on chamber CO 2 flux measurements were taken with dark chambers or at night for only ecosystem respiration.…”
Section: Resultsmentioning
confidence: 99%
“…The selection of observation time for chamber measurements was empirical in the literature. For instance, the observation length of CO 2 flux estimation ranged between 1.5 min to 10 min (Wohlfahrt et al, 2005; Kutzbach et al, 2007; Savage et al, 2008; Koskinen et al, 2014; Görres et al, 2016; Guidolotti et al, 2017; Kostyanovsky et al, 2018), and that of other green house gases such as CH 4 and N 2 O ranged between 10 min to 25 min (Hendriks et al, 2007; Kroon et al, 2008; Savage et al, 2014). Most of the published studies on chamber CO 2 flux measurements were taken with dark chambers or at night for only ecosystem respiration.…”
Section: Resultsmentioning
confidence: 99%
“…With no significant effect recorded in SR, and a limited (not significant) increase in TER, NEE stimulation mainly depended on the higher GP of vegetation in the NEE collars. Gross photosynthesis displayed strong seasonality, being lowest during the summer dry period and highest in spring and autumn (Guidolotti et al, 2017 ). The warming effect was restricted to these periods of optimal environmental conditions, and therefore did not depend on a different response to the summer aridity triggered by the temperature increase.…”
Section: Discussionmentioning
confidence: 99%
“…Shrubland CO 2 exchange was measured using transparent canopy chambers fitted with square NEE soil collars (0.64 m 2 ) connected to an LI‐8100 infrared gas analyzer (LI‐COR Biosciences, Inc.), following Guidolotti et al ( 2017 ). Two NEE collars were installed in each plot (six per treatment) during winter 2009, after 8 years of continuous temperature manipulation.…”
Section: Methodsmentioning
confidence: 99%
“…If there is no climate regulation, it is more difficult to maintain the temperature change in the closed chamber in the range of 2 • C [1]. Through research, Gabriele developed a dynamic closed chamber that can effectively monitor the CO 2 exchange dynamics of bushes [21]. The coverage area of the chamber is 0.64 m 2 (length and width are 0.8 × 0.8 m).…”
Section: Air Temperature and Humidity Changes Inside And Outside The ...mentioning
confidence: 99%
“…Droesler [6] used the dynamic closed chamber method to measure NEE of bog and their research showed that the maximum change of humidity during the measurement period reaches 20%. The relative humidity increase in the chamber designed by Gabriele [21] ranged between 4 and 20% in the CO 2 exchange measurement period, and the average value of humidity increase was 13%. Due to the use of the humidity control system, the maximum humidity change in the chamber developed in this study was 5.6% in the experiments.…”
Section: Air Temperature and Humidity Changes Inside And Outside The ...mentioning
confidence: 99%